Problems of Myanmar Women of Reproductive Age in Accessing Health Services as Migrant Workers in Thailand: A Qualitative Study - Sitkulanan, Piyaporn; Chaisitsanguan, Kunnikar; Winaiprasert, Prakaipetch; Wong-arsa, Wilailuck (Nurse Media Journal of Nursing, 2024)
Background: The largest portion of migrant labor in Thailand originates from Myanmar, with almost half consisting of female workers. Most female migrant workers (MWs) are of reproductive age and often experience physical illnesses, including pregnancy and childbirth. Although access to prenatal care and delivery services for Myanmar MWs has been previously studied, their challenges in accessing other reproductive health services (HSs) have not yet been explored.Purpose: This study aimed to explore problems in accessing health services experienced by women of reproductive age (WRA) who were members of the Myanmar migrant workforce in Thailand.Methods: The present study employed a qualitative research design. The samples consisted of 20 informants aged 18-49 years old, who were Myanmar WRA working as migrant laborers for more than one year. They were subdivided into two groups: 10 participants provided information through in-depth interviews, and the other 10 participated in focus group discussions, with each group comprising 5 individuals. The researchers selected informants using criterion sampling. Data analysis utilized the Diekelmann and Allen method.Results: The findings revealed two general themes, including care ineligibility and problems in accessing health services. The six major issues among Myanmar WRA include inability to purchase or renew health insurance cards (HICs), HIC or social security wage deduction avoidance, communication issues, hospital inexperience, the transit fare, and admission refusal.Conclusion: Despite available health services, migrant women from Myanmar encounter barriers such as inability to purchase health insurance cards, wage deduction concerns, communication issues, hospital unfamiliarity, transportation expenses, and admission refusal. Addressing these barriers through policy interventions and support mechanisms is crucial for enhancing healthcare access.